(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify the symbolic dimensions and the mechanisms of their employment in postmodern drawings. The research is determined by the spatial boundaries (United States of America and Europe) and the temporal boundaries (1945-2013). As for the objective boundaries, they are the analysis of pictorial models of paintings executed with different materials on different materials, represented by the school of abstract expressionism, folk art, body art, and graffiti art.